2019
DOI: 10.1111/1467-9566.13051
|View full text |Cite
|
Sign up to set email alerts
|

Exploring health behaviours: understanding drinking practice using the lens of practice theory

Abstract: Research suggests that there is no safe amount of alcohol but despite this alcohol consumption remains an important part of many [young] people's lives. Viewed as an inherently social activity, drinking alcohol provides an opportunity for socialising and connecting with friends. This study is one of the first to draw on practice theory to explore one type of intoxicated drinking occasion engaged in by young people; framed in this article as a ‘proper night out’. This article argues that this hybrid entity is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Alongside these hypotheses, and potentially part of the reason for mixed results, is that the rise of the internet has provided a new mechanism for alcohol marketing to young people by redefining social norms around drinking and promoting active participation through features such as "stories" and "live feeds" (Carah, Brodmerkel, & Hernandez, 2014;Nicholls, 2012). Recent studies have also shown how internet-based technologies play a central role in coordination of social activities for young people (Hennell, Piacentini, & Limmer, 2020;Supski, Lindsay, & Tanner, 2017). However, empirical studies of the relationship between internet use and drinking or computer gaming and drinking have produced mixed results (Brunborg & Andreas, 2019;Brunborg, Mentzoni, & Frøyland, 2014;Erevik et al, 2019;Ream, Elliott, & Dunlap, 2011;Wenzel, Bakken, Johansson, Götestam, & Øren, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside these hypotheses, and potentially part of the reason for mixed results, is that the rise of the internet has provided a new mechanism for alcohol marketing to young people by redefining social norms around drinking and promoting active participation through features such as "stories" and "live feeds" (Carah, Brodmerkel, & Hernandez, 2014;Nicholls, 2012). Recent studies have also shown how internet-based technologies play a central role in coordination of social activities for young people (Hennell, Piacentini, & Limmer, 2020;Supski, Lindsay, & Tanner, 2017). However, empirical studies of the relationship between internet use and drinking or computer gaming and drinking have produced mixed results (Brunborg & Andreas, 2019;Brunborg, Mentzoni, & Frøyland, 2014;Erevik et al, 2019;Ream, Elliott, & Dunlap, 2011;Wenzel, Bakken, Johansson, Götestam, & Øren, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Phones and apps were central to how young people planned social events, mobilised themselves and their networks, and engaged in a range of social practices (including drinking). Indeed, as others have noted, phones have become a central feature of a 'night out', from organisation (pre-event) to drinking (event) to story-telling afterwards (postevent) (Hennell et al, 2020;Hutton et al, 2021). Here, they allowed young people to designate drinking as a central practice in events and made some drinking events more accessible.…”
Section: Discussionmentioning
confidence: 99%
“…In their interviews with Australian undergraduate students, Supski et al (2017) showed how university drinking was a distinct practice grouped with other practices that reinforced and normalised heavy drinking for students. Hennell et al (2020) used practice theory to explore drinking on 'a proper night out' among young people in North-West England. Their study highlighted how a night out was made up of a sequential 'bundle' of practices, including planning, getting ready, pre-drinking, going out, getting home and storytelling.…”
Section: Practice Theory In Alcohol Researchmentioning
confidence: 99%
“…see 3], pre‐drinking has been associated with higher levels of intoxication [4–6] and alcohol‐related risks and harm [7–12]. Pre‐drinking behaviour has also been increasing in prevalence over time [11,13], driven by changes in socialising behaviour [14] and by the price differential between alcohol purchased at on‐licensed venues and takeaway alcohol [15].…”
Section: Introductionmentioning
confidence: 99%
“…see 3], pre-drinking has been associated with higher levels of intoxication [4][5][6] and alcohol-related risks and harm [7][8][9][10][11][12]. Pre-drinking behaviour has also been increasing in prevalence over time [11,13], driven by changes in socialising behaviour [14] and by the price differential between alcohol purchased at on-licensed venues and takeaway alcohol [15]. Despite a growing significance of pre-drinking behaviour in the wider population, most extant studies of pre-drinking behaviour have been limited to student or young adult populations [e.g.…”
Section: Introductionmentioning
confidence: 99%